Religious Tourism of the Tomb of Syekh Maulana Syamsuddin as a Transformation of the Halal Industry in Improving the Economic Welfare of the Community of Widuri Pemalang - Muhammad Maskur Musa; Siti Salamah; Rizki Fauzi; M. Aba Yazid (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The role of the tourism industry is very important in efforts to build and develop an area. Even the tourism industry in some areas can improve the area’s underdevelopment and backwardness, as well as serve as the main source of regional income. The role of the tourism industry has resulted in a beneficial impact, including the area being crowded, creating jobs, and increasing regional income, so as to be able to create prosperity for the community. This study aims to explain the religious tourism of Syekh Maulana Syamsudin’s tomb as a transformation of the halal industry in improving the economic welfare of the community. The method used in this study is field research, with the research approach being a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation The results of his research show that the tomb of Syekh Maualana Syamsudin has become a site of religious tourism that is already well-known in Pemalang and the surrounding communities. Many people from Pemalang itself and people from outside the city come to make pilgrimages. so that the pilgrimage to the tomb of Syekh Maualana Syamsudin has become a tradition or habit for people from various regions. Moreover, the tomb of Syekh Maualana Syamsudin is very close to the widuri beach, so people not only make pilgrimages but also visit the beach. With so many people coming to the tomb for pilgrimages, as well as doing tours to this widuri beach, it provides an opportunity for the Pemalang community, especially those close to the tomb and beach areas, to open a business, namely selling food, clothing, or other accessories. This makes the Pemalang widuri community feel very helped by their economy, so that the economic welfare of the Pemalang widuri community can increase in their daily lives.